2021
DOI: 10.1029/2021gc010029
|View full text |Cite
|
Sign up to set email alerts
|

Three‐Dimensional Electrical Resistivity Characterization of Mountain Pass, California and Surrounding Region

Abstract: Rare earth elements (REE) have atomic numbers ranging from 57 to 71, commonly referred to as the "lanthanides." These elements have unusual chemical and physical properties that make them useful for a variety of technologies ranging from batteries to magnets to glass polishes (Gosen et al., 2017). REEs are common in crustal abundance, however large concentrations of REE are not, making it important to identify resources as global demand increases (Gosen et al., 2017). Large REE deposits are often associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 72 publications
(203 reference statements)
0
2
0
Order By: Relevance
“…However, the values of | β| increase at periods greater than 1 s, implying the presence of a complex 3‐D geoelectric structure in the middle‐lower crust. The orientation of the principal axis of the phase tensor in the WSSZ is NW–SE, which is either parallel or perpendicular to the geological strike due to the 90° ambiguity in the polarization of electromagnetic fields (Booker, 2014; Peacock et al., 2021). Overall, the phase tensor results show significant 3‐D structural features along the MT profile, and thus, the 3‐D inversion and interpretation of the MT data from this profile are essential for realistically imaging the subsurface electrical structure.…”
Section: Mt Data and Processingmentioning
confidence: 99%
“…However, the values of | β| increase at periods greater than 1 s, implying the presence of a complex 3‐D geoelectric structure in the middle‐lower crust. The orientation of the principal axis of the phase tensor in the WSSZ is NW–SE, which is either parallel or perpendicular to the geological strike due to the 90° ambiguity in the polarization of electromagnetic fields (Booker, 2014; Peacock et al., 2021). Overall, the phase tensor results show significant 3‐D structural features along the MT profile, and thus, the 3‐D inversion and interpretation of the MT data from this profile are essential for realistically imaging the subsurface electrical structure.…”
Section: Mt Data and Processingmentioning
confidence: 99%
“…Electromagnetic methods have been extensively employed in the exploration of ore deposits, including rare earth mineral exploration [21], as well as the exploration of coppernickel deposits [22], lead-zinc ore deposits [23], and gold deposits [24]. These research endeavors have effectively demonstrated the potential applications of electromagnetic techniques in mineral exploration.…”
Section: Introductionmentioning
confidence: 99%